Assessing and promoting resilience in vulnerable children. - Daniel, Brigid, 1959- (Assessing and promoting resilience in vulnerable children ;, 2002)
This practical resource for work with vulnerable adolescents shows ways of promoting resilience and encouraging pro-social behaviour. Discussing concerns associated with adolescence such as peer pressure and moral responsibility and family and peer relationships, the authors suggest ways for practitioners to engage with and support young people who may have social or family problems. Focusing on different areas in which resilience can be cultivated, this practical guide offers an applied perspective on procedures of need assessment and intervention. Grounded in theory and developed through wor.